RLWE-based key-policy ABE scheme - Ze-dong SUN; Yue-fei ZHU; Chun-xiang GU; Yong-hui1 ZHENG (Tongxin xuebao)
Based on the attribute-based encryption(ABE) scheme which was proposed by Brakerski and constructed on the LWE problem,a RLWE-based key-policy ABE scheme was presented.Efficiency and key size of this scheme over-takes old ones which are based on the LWE problem.Under the RLWE assumption,this scheme supports attributes of unbounded length and semi-adaptive security.Moreover,a compiler was constructed and could compile ABE scheme that meets its demand into an attribute-based fully homomorphic encryption (ABFHE) scheme.